Identifikasi Senyawa Metabolit Sekunder pada Ekstrak Daun Gayam (Inocarpus Fagifer Fosb) dengan Menggunakan KLT - Rohama Rohama; Zainuddin Zainuddin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The Gayam tree is widespread in the territory of Indonesia, the Gayam plant (Inocarfus Fegifer Fosb) is also used as a medicine for bloody bowel movements in the community by boiling the stems and drinking boiled water. Besides having medicinal properties, Gayam is also used as food in the community in the Banjarmasin area. The common people certainly do not know the benefits of gayam and its nutritional value. Research on the identification of secondary metabolite compounds in Gayam leaf extract (Inocarpus Fagifer Fosb) using TLC where Gayam Leaves (Inocarpus Fagifer Fosb) was extracted by maceration method, the thick extract obtained was then carried out by testing the identification of secondary metabolites with color reagent and TLC. The results of the identification of the compound metabolite of gayam leaves (Inocarfus Fegifer Fosb) by color reagent and TLC test showed positive test results for alkaloids, flavonoids, terpenoids, saponins.